Answer:
Explanation:
The given expression is
{y=2x2+2x+1} {y=2x+3}
y =2x^2 + 2x + 1 - - - - - - - - 1
y =2x + 3 - - - - - - - - -2
We would equate equation 1 to equation 2, it becomes
2x^2 + 2x + 1 = 2x + 3
2x^2 + 2x + 1 = 2x + 3
We would subtract 2x from the left hand side of the equation and the right hand side of the equation. It becomes
2x^2 + 2x - 2x + 1 = 2x - 2x + 3
2x^2 + 1 = 3
We would subtract 1 from the left hand side of the equation and the right hand side of the equation. It becomes
2x^2 + 1 - 1 = 3 - 1
2x^2 = 2
Dividing through by 2, it becomes
x^2 = 1
Taking square root of both sides,
x = ±1